What do changes in prematch vs. postmatch, 1, 2, and 3 days postmatch body weight tell us about fluid status in English Premiership Rugby Union players? - Meir, R. A.; Brooks, L. O.; Rogerson, S. (The Journal of Strength and Conditioning Research, 2011)
This study investigated changes in body weight pre and postmatch and 1, 2, and 3 days postmatch. Thirty-six players contracted to an English Premiership rugby union club had their pre and postmatch body weight and 1, 2, and 3 day postmatch body weight recorded across 14 matches played (10 at home and 4 away) during the official 2003-2004 professional rugby union season, representing a total of 262 player appearances. Body weight was recorded using a set of calibrated Seca digital scales with players wearing underwear only and toweled dry of all sweat (postmatch). Players were allowed to ingest fluid ad libitum throughout each match. A number of players recorded pre to postmatch reductions of body weight of >2% with some as high as 4.9%. Significant position-specific mean reductions in prematch to postmatch body weight (±SD) were found for both forwards (1.94 ± 0.14 kg) and backs (1.04 ± 0.17 kg). The mean gain in postmatch to 1-day postmatch body weight was significant for forwards (1.40 ± 0.27 kg) but not for backs (0.76 ± 0.30 kg). There were no significant mean differences between prematch and 2 or 3 days postmatch body weight for either forwards or backs. Forwards on average lost a significantly greater proportion of their weight pre to postmatch than backs (p = 0.005). Forwards were on average 99.5% of the prematch weight at 1 day postmatch, whereas backs were 99.7% (p = 0.598). Forwards were 99.6% of their prematch weight at 3 days postmatch, whereas backs were 100.4% (p = 0.035). Changes in fluid status can be effectively monitored by recording changes in body weight and is useful where players are undertaking training sessions within 1, 2, or 3 days after their last match as a measure of rehydration status.